2022
DOI: 10.1111/ppc.13069
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Alzheimer's blanket activity program on behavioral symptoms, activities of daily living, and quality of life

Abstract: Purpose: The study was conducted to evaluate the effects of the Alzheimer's blanket activity program (ABAP) on the behavioral symptoms, activities of daily living, and quality of life of people with Alzheimer's disease. Design and Method:The study was conducted between November 2019 and February 2020 in the homes of the participants with Alzheimer's disease with a single group pre-post-test design. As part of the ABAP, the researchers made two home visits, conducted telephone interviews, and provided counselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…[36] Because of the advantage on a lower incidence rate of AEs, atypical antipsychotics have been more widely used than typical ones. [4,37,38] There was a systematic review reported that atypical antipsychotics including olanzapine and risperidone were effective in treatment of BPSD comparing to placebo. However, quetiapine was not considered effective in that pooled analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[36] Because of the advantage on a lower incidence rate of AEs, atypical antipsychotics have been more widely used than typical ones. [4,37,38] There was a systematic review reported that atypical antipsychotics including olanzapine and risperidone were effective in treatment of BPSD comparing to placebo. However, quetiapine was not considered effective in that pooled analysis.…”
Section: Discussionmentioning
confidence: 99%